Multiple rotational rates in a guest-loaded, amphidynamic zirconia metal–organic framework. Issue 42 (7th October 2020) - Torres-Huerta, Aaron; Galicia-Badillo, Dazaet; Aguilar-Granda, Andrés; Bryant, Jacob T.; Uribe-Romo, Fernando J.; Rodríguez-Molina, Braulio
Abstract : Zirconia based metal–organic framework PEPEP-PIZOF-2 exhibits the emergent property of amphidynamic motion with organic links that show multiple rotational rates related to their molecular structure and independently from presence of molecular guests. Abstract : Amphidynamic motion in metal–organic frameworks (MOFs) is an intriguing emergent property, characterized by high rotational motion of the phenylene rings that are embedded within an open, rigid framework. Here, we show how the phenylene rings in the organic linkers of the water stable MOF PEPEP-PIZOF-2 exhibit multiple rotational rates as a result of the electronic structure of the linker, with and without the presence of highly interacting molecular guests. By selective 2 H enrichment, we prepared isotopologues PIZOF-2 d 4 and PIZOF-2 d 8 and utilized solid-state 13 C and 2 H NMR to differentiate the dynamic behavior of specific phenylenes in the linker at room temperature. A difference of at least one order of magnitude was observed between the rates of rotation of the central and outer rings at room temperature, with the central phenylene ring, surrounded by ethynyl groups, undergoing ultrafast 180° jumps with frequencies higher than 10 MHz. Moreover, loading tetracyanoquinodimethane (TCNQ) within the pores produced significant changes in the MOF's electronic structure, but very small changes were observed in the rotational rates, providing an unprecedented insight into the effects that internal dynamics have on guest diffusion. These findings would help elucidate the in-pore guest dynamics that affect transport phenomena in these highly used MOFs.